2014
DOI: 10.1016/j.ultsonch.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of microorganisms by low-frequency high-power ultrasound: 1. Effect of growth phase and capsule properties of the bacteria

Abstract: The aim of this study was to determine the effects of high-intensity low-frequency (20 kHz) ultrasound treatment on the viability of bacteria suspension. More specifically, we have investigated the relationship between the deactivation efficiency and the physical (size, hydrophobicity) and biological (gram-status, growth phase) properties of the microbes. Enterobacter aerogenes, Bacillus subtilis, Staphylococcus epidermidis, S. epidermidis SK and Staphylococcus pseudintermedius were chosen for this study owing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(118 citation statements)
references
References 60 publications
6
99
2
2
Order By: Relevance
“…Our findings and those of Al Bsoul et al might be due to various effects on the medium through which these mechanisms offset each other. We also observed that the Gram-negative bacterium E. coli was more sensitive to ultrasound treatment than the Gram-positive bacterium S. aureus (Table 1), a finding that was in accordance with previously published studies (37)(38)(39)(40). According to the literature, this result might be due to the thicker and more tightly adherent layer of peptidoglycan in Gram-positive cells (41).…”
Section: Enumeration Of Surviving Cells By Plate Counts (Cultivability)supporting
confidence: 92%
“…Our findings and those of Al Bsoul et al might be due to various effects on the medium through which these mechanisms offset each other. We also observed that the Gram-negative bacterium E. coli was more sensitive to ultrasound treatment than the Gram-positive bacterium S. aureus (Table 1), a finding that was in accordance with previously published studies (37)(38)(39)(40). According to the literature, this result might be due to the thicker and more tightly adherent layer of peptidoglycan in Gram-positive cells (41).…”
Section: Enumeration Of Surviving Cells By Plate Counts (Cultivability)supporting
confidence: 92%
“…Gao et al have confirmed that the inactivation of microorganisms is due to shear forces generated by collapse of cavitation bubbles [39,40]. Given this background and our own experimental results, we consider that physical effects are responsible for algae disruption under ultrasonication in the present study.…”
Section: Physical Effectsmentioning
confidence: 59%
“…It has been observed that ultrasound was more effective in destroying the gram negative bacteria (Enterobacter aerogenes) than gram positive bacteria (Staphylococcus spp). The latter is not much affected due to the resistance from the capsules [12]. The use of ultrasound by itself may not be effective in destroying all the microbes in food.…”
Section: Discussionmentioning
confidence: 99%